PVA/PVP Dissolving Microneedle Arrays Loaded with Parameria laevigata Extract: Formulation and Characterization for Transdermal Anti-Acne Therapy - Angga Yasir; Siwi Nurbaiti; Jenifer Kolina; Amalia Lathifah Widiadari; Harmiansyah; Muhammad Asyraf Muhammad Rizal; Melbi Mahardika (Research Center of Inorganic Materials and Coordination Complexes, FMIPA Universitas Sriwijaya, 2026)
Despite the well-documented antimicrobial and antioxidant properties of Parameria laevigata (kayu rapet) bark, its incorporation into a dissolving microneedle (DMN) platform for transdermal acne therapy has not been previously investigated. This study developed and characterized PVA/PVP-based DMN arrays loaded with P. laevigata extract as a minimally invasive delivery system targeting acne-associated pathogens. Ultrasonic-assisted extraction in 95% ethanol yielded a phytochemical-rich extract (8.68%) containing flavonoids, tannins, saponins, and alkaloids, with strong antioxidant activity (DPPH IC50 = 40.98 ± 4.32 ppm; ABTS IC50 = 46.92 ± 3.25 ppm; FRAP = 70.24 ± 6.41 mg AAE/g extract) and moderate antibacterial activity against Acne vulgaris-associated bacteria Staphylococcus aureus and Cutibacterium acnes at 100–150 ppm (inhibition zone: 8.22–8.46 mm). Eight DMN formulations were fabricated at a fixed 30% w/w PVA/PVP total polymer concentration with 5% extract loading. The optimized formulation (F2) produced a complete 49-needle pyramidal array with adequate mechanical integrity for stratum corneum penetration, confirmed polymer–extract physicochemical compatibility by FTIR, and exhibited Korsmeyer–Peppas release kinetics with a diffusion-controlled mechanism reaching 56.48% cumulative release over 24 h. These findings establish P. laevigata-loaded DMN arrays as a viable proof-of-concept platform for transdermal acne therapy, warranting further ex vivo permeation and in vivo efficacy validation.